Effectiveness of Nurse Led Intervention Regarding Management of Hypertension on Awareness, Treatment Compliance, Life Style and Quality of Life among Hypertensive Adults: A Systematic Review - Eenu; Poonam Sheoran; Jyoti Sarin (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: Hypertension is one of the most common conditions affecting the health worldwide and isalso the leading cause of death around the globe. There is a persistent need for effective nurse led interventionfor interrupting the further spreading roots of the hypertension in the community. There is also a great needfor creating awareness, ensuring the compliance with the treatment, modification of lifestyle and improvingthe quality of life for the sufferers of this condition.Methods: The study design was systematic review and it includes studies from databases of PUBMED,MEDLINE, Cochrane library, SCOPUS, Science direct, and Google scholar (2008-2019). The includedstudies were focusing on the management of hypertension among hypertensive adults in terms of awareness,treatment compliance, life style and quality of life.Result: The data was grouped and analyzed in terms of meta-analysis. Total 20 relevant articles wereundertaken. Abstracted information is related to study design, population characteristics, intervention andoutcomes.Conclusion: The nurse led intervention in the management of hypertension is an effective strategy inimproving the health outcomes in terms of creating awareness, ensuring the compliance with the treatment,modification of life style and improving the quality of life among hypertensive adults.